2023
DOI: 10.1063/1674-0068/cjcp2202032
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Empirical model to retrieve finite temperature terahertz absorption spectra using Morse potential

Abstract: Terahertz (THz) absorption is a fingerprint property of materials, due to the underlying low-frequency vibration/phonon modes being strongly dependent on the chemical constitutions and microscopic structures. The low excitation energies (0.414−41.4 meV) are related to two intrinsic properties of THz vibrations: the potential energy surfaces (PESs) are shallow, and the vibrationally excited states are usually populated via thermal fluctuations. The shallow PESs make the vibrations usually anharmonic, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Due to the high transmittance of THz waves in crude oil, it can measure the amplitude attenuation and time delay of the incident terahertz pulse without sample pretreatment, making it operationally simple. Additionally, the THz-TDS can be applied to analyze the compound structures and intermolecular interaction among organic molecules (such as hydrogen bonding, Van der Waals forces, dipole rotation, and vibrational transitions) [28][29][30][31]. It has been demonstrated that THz-TDS is applicable in qualitative and quantitative analysis of the crude oil properties [32,33], but its application in crude oil classification has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high transmittance of THz waves in crude oil, it can measure the amplitude attenuation and time delay of the incident terahertz pulse without sample pretreatment, making it operationally simple. Additionally, the THz-TDS can be applied to analyze the compound structures and intermolecular interaction among organic molecules (such as hydrogen bonding, Van der Waals forces, dipole rotation, and vibrational transitions) [28][29][30][31]. It has been demonstrated that THz-TDS is applicable in qualitative and quantitative analysis of the crude oil properties [32,33], but its application in crude oil classification has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz (THz) vibrational spectroscopy is a powerful technique for detecting low frequency vibration modes 1–3 and intermolecular interactions in the condensed phase. 4,5 The very low photon energy of THz waves (∼4.1 meV for 1 THz), which is much lower than the bonding or ionization energies of conventional molecules, enables the non-destructive detection and characterization. 6,7 Moreover, because of the high sensitivity to intra- and inter-molecular structures, THz spectroscopy has a fingerprint characteristic, which is effective in the detection of isomers and other similar substances.…”
Section: Introductionmentioning
confidence: 99%